Evaluasi E-Medrec pada Bagian Analisis Rekam Medis Kuantitatif Rawat Inap di Rumah Sakit TK II Dustira Cimahi - Aulia Zeta Andhani; Setiatin, Sali; Ningrum, Intan Septiana (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Background: Quantitative analysis at Rumah Sakit TK II Dustira Cimahi is carried out by 2 (two) methods, namely manually using files and electronically through the E-Medrec application, where it is necessary to assess whether these activities have reached the standard and the aim is to find out whether there are obstacles or obstacles in their implementation, so that improvements can be made. Objective: To evaluate the implementation of the use of E-Medrec in the implementation of quantitative analysis of inpatient medical records at Rumah Sakit TK II Dustira Cimahi. Research Methods: The method used in this research is qualitative analysis with a descriptive approach using the TAM (Technology Acceptance Model) research model, researchers examine 3 aspects, namely aspects of usefulness (Perceived Usefulness), aspects of ease of use (Perceived Ease Of Use), and aspects of behavioral interest (Attitude Towards Behavior). Results: The results of data collection collected through questionnaires were processed and then converted into a percentage form to describe the results of the implementation of E-Medrec in the quantitative analysis of inpatient medical records. Conclusion: In the aspect of perceived usefulness, namely the perceived usefulness of E-Medrec, all respondents have good indicators. In the aspect of perceived ease of use, namely the perception of ease, all respondents have adequate indicators. In the aspect of attitude towards behavior, namely attitude / interest in using E-Medrec, all respondents have good indicators. The implementation of E-Medrec that has been running can be used as a consideration in planning the development and implementation of health information systems.